Bio‐Assisted Tailored Synthesis of Plasmonic Silver Nanorings and Site‐Selective Deposition on Graphene Arrays. Issue 4 (20th December 2019) - Giovannini, Giorgia; Ardini, Matteo; Maccaferri, Nicolò; Zambrana‐Puyalto, Xavier; Panella, Gloria; Angelucci, Francesco; Ippoliti, Rodolfo; Garoli, Denis; De Angelis, Francesco
Abstract: The spontaneous interaction between noble metals and biological scaffolds enables simple and cost‐effective synthesis of nanomaterials with unique features. Here, plasmonic silver nanorings are synthesized on a ring‐like protein, i.e., a peroxiredoxin (PRX), and used to assemble large arrays of functional nanostructures. The PRX drives the seeding growth of metal silver under wet reducing conditions, yielding nanorings with outer and inner diameters down to 28 and 3 nm, respectively. The obtained hybrid nanostructures are selectively deposited onto a solid‐state 2D membrane made of graphene in order to prepare plasmonic nanopores. In particular, the interaction between the graphene and the PRX allows for the simple preparation of ordered arrays of plasmonic nanorings on a 2D‐material membrane. This fabrication process can be finalized by drilling a nanometer scale pore in the middle of the ring. Fluorescence spectroscopic measurements in combination with numerical simulations demonstrate the plasmonic effects induced in the metallic nanoring cavity. The prepared nanopores represent one of the first examples of hybrid plasmonic nanopore structures integrated on a 2D‐material membrane. The diameter of the nanopore and the atomically thick substrate make this proof‐of‐concept approach particularly interesting for nanopore‐based technologies and applications such as next‐generation sequencing and single‐molecule detection. Abstract : A new hybrid plasmonic nanopore is presented here. A biological template can be easily used to prepare silver rings that can be arranged over graphene to create narrow cavities with high enhanced electromagnetic field.